RETRACTED ARTICLE: Experimental study and numerical prediction of HTO and 36Cl− diffusion in radioactive waste at Téguline Clay. Issue 17 (29th July 2022) - Zhang, Yun-yi; He, Yong; Li, Bing-bing; Zhang, Ke-neng
Abstract : Statement of Retraction: Experimental study and numerical prediction of HTO and 36Cl− diffusion in radioactive waste at Téguline Clay We, the Editor and Publisher of Environmental Technology, have retracted the following article: Yun-yi Zhang, Yong He, Bing-bing Li & Ke-neng Zhang, Experimental study and numerical prediction of HTO and 36Cl− diffusion in radioactive waste at Téguline Clay, Environmental Technology, Latest Articles, 10.1080/09593330.2021.1939433 Following publication, errors have been identified in the experimental work and numerical simulation as follows: 1) The experimental results presented in this paper are too limited to effectively support the numerical analysis. 2) Although XRD, MIP, SEM and other microstructural tests were conducted and presented in this paper, the results of these microstructural tests have not been used in the numerical analysis, leading to incorrect results shown in Figure 11. 3) There is a serious discrepancy between the simulated results and the real conditions, due to an incorrect selection of diffusion parameters and initial concentration (200 mg/L and 500 mg/L) as well as an incorrect simulation model and boundary condition (Figure 4). 4) The simulation software (Geo-studio + MATLAB) appears to be unsuitable for the simulation work in this paper due to physical, mechanical and adsorption properties of the sample not being considered in the simulation. These errors were identified and acknowledged by the authors. The errors are too substantial to be corrected in a corrigendum and will alter the conclusions of the paper. There are no concerns regarding research or publishing conduct, and the authors plan to revisit the relevant mature results of their research and may resubmit the revised paper for consideration by the journal. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as "Retracted".